Vaccine prophylaxis of pneumococcal infection among premature infants with bronchopulmonary dysplasia - Vladislav SEMERICOV (Asociatia de Biosiguranta si Biosecuritate, 2020)
Introduction. Bronchopulmonary dysplasia (BPD) is the most common chronic lung disease among children of the first year of life, especially children born prematurely with extremely low and very low body weight. Material and methods. To estimate the number of children born alive in the Perm Territory between 2015 and 2017, official statistics data were used. Experimental epidemiological studies were used to assess safety, reactogenicity, immunogenic activity, and preventive efficacy of the Prevnar 13 vaccine when immunizing preterm infants with bronchopulmonary dysplasia under prospective controlled randomized clinical observation. Results. There were 29 premature infants with bronchopulmonary dysplasia under observation, the control group comprised 29 unvaccinated premature infants with BPD and 30 full-term infants. The PCV 13 vaccination of preterm infants with BPD established good tolerance, poor reactogenicity (17.2±0.57%), and vaccine tolerance like full-term infants (16.5±0.55%), high safety profile, high immunogenic properties (seroconversion – 93.1%, seroconversion factor – 5.5). Evaluation of immunogenic activity among children with BPD vaccinated with the PCV 13 vaccine revealed high immunological efficacy compared to unvaccinated healthy children. Conclusion. The need for vaccination of premature babies with BDL against pneumococcal infection has been scientifically substantiated. The study has confirmed safety, poor reactogenicity, high immunogenic activity, and preventive efficacy of the Prevenar 13 vaccine among premature babies with BDL under the conditions of the catamnesis department of the perinatal center within the follow-up monitoring of vaccinated infants over three years.